Relevant aspects of legal education in the dissertation researches of contemporaries (Pedagogy of Higher and Secondary Education, 2016)
Vysotska L. V. Relevant aspects of legal education in the dissertation researches of contemporaries.The article reviews the current scientific dissertations to determine the state of legal education.Leagal education is a part of the educational system of Ukraine. It is the set of educational, training and information measures aimed at establishement of conditions for receiving leagal knowledge and skills by citizens. They are necessary for citizens to exercise their rights and freedoms as well as to perform their duties [7]. This is the essence of the eprogram, whose purpose and objectives are identified in the «Legal Education Program of the population of Ukraine» (approved by the Council of Ministers of Ukraine, №366 from 05.29.1995 p.; new edition of 21.08.2012 g.).The purpose of the article is to find out the nature of coverage of issues related to legal education in domestic dissertations, reflecting the state of general scientific problems in the modern pedagogical discourse.A significant number of scientific materials prove that researchers focuse attention on the following aspects of legal education: history of formation and development of legal education, legal education of future teachers, the legal competence of other specialists, theory and content of legal education.For many years of theoretical and methodological studies in the field of law different legal concepts, based on the author’s approach (theoretical and practical, encyclopedic, specialized, practice-oriented, etc.) to the content of legal disciplines, their methodological support and learning technologies have been formed [6]. However, modern scholars rarely chose conceptual aspect of the program as a subject of a separate study. They mainly use experience of their predecessors.As a result of analysis of scientific and pedagogical discourse it was determined that modern scholars studying issues related to legal education prefer the following aspects: «legal education», «legal competence», «legal concept». It has been determined that these aspects of the modern scientific and pedagogical discourse are still fragmented, so scientists avoide to clarify the multidimensional definition of «legal education». Determination the essence of these concepts is a promising direction for future researches.
Keywords: legal; legal education; legal competence; legal concept; pedagogical discourse